Cosa resta degli angeli?: Una rilettura della novella di Fra’ Alberto (Decameron IV, 2), tra le maschere dell’angelo e dell’uom salvatico - Andreaux, Patrizio Alberto (Incontri. Rivista europea di studi italiani, 2014)
What remains of angels?: A re-reading of the novel of Fra’ Alberto (Decameron IV, 2), between the masks of the angel and the uom selvatico Boccaccio’s novel about brother Alberto is usually considered an amusing divertissement presented by the author himself as a contrast to the preceding tragic novel involving Tancredi and Ghismunda. A much more serious meaning can be found, however, beyond the comic facet, this being a deep and somewhat bitter vision of a man living in the Late Middle Ages, lost between the earthly and heavenly dimension. This article exploits the well known visual aspects of Boccaccio’s novels and focuses on the visual representation of the main character and its iconographical connotations, which in certain cases seems to fill up the silence of the text. Two of Alberto’s masks (the intentional mask of the angel and the punitive mask of ‘uom salvatico’) appear imperfect, provisional and actually overlap one other. This image places both the real and fictional identities of the character at risk and converges them in a sort of final metamorphosis and equation. On a textual level, this concept is supported by the high incidence of the terms ‘agnolo’ and ‘salvatico’, as well as by a pun based on a false etymological affinity between ‘salvatore’ and ‘salvatico’ (the same used by Edmund Spenser in his The Faerie Queene).